1999
DOI: 10.1073/pnas.96.21.12150
|View full text |Cite
|
Sign up to set email alerts
|

RNA diversity has profound effects on the translation of neuronal nitric oxide synthase

Abstract: A comprehensive analysis of the structure of neuronal nitric oxide synthase (nNOS; EC 1.14.13.39) mRNA species revealed NOS1 to be the most structurally diverse human gene described to date in terms of promoter usage. Nine unique exon 1 variants are variously used for transcript initiation in diverse tissues, and each is expressed from a unique 5-flanking region. The dependence on unique genomic regions to control transcription initiation in a cell-specific fashion burdens the transcripts with complex 5-mRNA l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
148
2
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 173 publications
(163 citation statements)
references
References 33 publications
9
148
2
4
Order By: Relevance
“…The quantitative discrepancy between RNA and protein levels can be best explained by the fact that RNA and protein levels are regulated by distinct mechanisms. These involve control at the level of both synthesis and stability and are discussed in Wang et al 25 Consistent with our findings in bladder cancer cell lines, quantitative PCR analysis of 28 primary bladder cancer tissue samples also revealed that CXCR4 was the only chemokine receptor whose mRNA expression levels correlated with tumor stage. High mRNA levels of CXCR4 were seen in invasive and locally advanced bladder cancer (pT2-pT4).…”
Section: Discussionsupporting
confidence: 91%
“…The quantitative discrepancy between RNA and protein levels can be best explained by the fact that RNA and protein levels are regulated by distinct mechanisms. These involve control at the level of both synthesis and stability and are discussed in Wang et al 25 Consistent with our findings in bladder cancer cell lines, quantitative PCR analysis of 28 primary bladder cancer tissue samples also revealed that CXCR4 was the only chemokine receptor whose mRNA expression levels correlated with tumor stage. High mRNA levels of CXCR4 were seen in invasive and locally advanced bladder cancer (pT2-pT4).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, human Nos1 is distributed over 160 kb among 29 exons and 28 introns, with nine recognized splice variants in the neuronal tissue cluster (Nos1a-i) regulated by alternate promoter usage in the 5' untranslated region flanking the first exon (Wang et al, 1999;Xie et al, 1995). Of these, Nos1f and Nos1g are predominantly expressed in brain (Wang et al, 1999). Although similar in both size and organization, mouse Nos1 has been much less studied than the human gene and far less is known regarding regulation of inducible expression of different splice variants.…”
Section: Discussionmentioning
confidence: 99%
“…12 At least nine unique exon 1 variants from the upstream region are used to initiate transcription in a tissue/cell-specific manner through usage of alternative promoters. 13 Interestingly, those exon 1 variants enriched in neuronal tissues are clustered in one genomic region whereas those enriched in skeletal muscle are grouped together in another genomic region 75 kb upstream, 13 indicating distinct transcriptional regulatory mechanisms. In addition, it is possible that the human nNOS gene also contains an exon 2 promoter that is analogous to the novel, calciumresponsive exon 2 promoter recently characterized in the rodent.…”
mentioning
confidence: 99%